A novel SLC44A gene variant in a patient with neonatal cholestasis and liver failure - Barut, Dogan; Dörtkardeşler, Emine Burçe; Karakoyun, Miray; Canda, Ebru; Onay, Huseyin; Aydogdu, Sema (Molecular genetics and metabolism reports, 2025)
SLC44A1 gene variants (MIM # 618868) are associated with a choline transporter deficiency with a rare autosomal recessive genetic disorder characterized by neurodegeneration, childhood-onset with ataxia, tremor, optic atrophy, and cognitive decline. Variants in the SLC44A1 gene are considered to be responsible for the syndrome. We reported a four-month-old baby with neonatal cholestasis and liver failure, but neurological development and examination were normal. During the patient's initial physical examination, height, weight, and head circumference were < −2 SDS. He was alert, with eye tracking and a smile present, appeared icteric, and exhibited hepatosplenomegaly, with a history of second-degree consanguinity between his parents. The patient showed signs of neonatal jaundice, elevated transaminases, and episodes of hypoglycemia. After excluding biliary atresia, tyrosinemia, and other metabolic diseases, mitochondrial hepatopathy, vascular pathologies, and congenital infectious diseases through all standard examinations for neonatal cholestasis, a genetic analysis test and whole exome analysis were conducted. Molecular analysis of the whole exome revealed a novel inherited mutation, one inherited from each parent. This novel variant in the SLC44A1 gene is c.1632 + 1G > A. A thorough physical examination and laboratory tests should be conducted for patients presenting with neonatal cholestasis. Subsequently, whole exome analysis from the parents identified the same mutation as heterozygous c.1632 + 1G > A in the SLC44A1 gene. Genetic examinations should be considered in patients whose cause remains undetermined, particularly when there is a family history. We describe a novel childhood-onset liver failure and metabolic disease caused by choline transporter deficiency with autosomal recessive inheritance.